2009
DOI: 10.3233/ip-2009-0170
|View full text |Cite
|
Sign up to set email alerts
|

The formation of inter-organizational information sharing networks in public safety: Cartographic insights on rational choice and institutional explanations

Abstract: In this article we offer visual depictions and analysis of contextual factors relative to the presence of public safety networks (PSNs) in the United States (US). A PSN combines shared technological infrastructures for supporting information sharing, computing interoperability and interagency interactions involving policing, criminal justice, and emergency response. The broad research objective is to explain the formation of PSNs based upon factors derived from rational choice and institutional theories. To do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 40 publications
0
20
0
Order By: Relevance
“…Networks of public and private organizations are commonplace in Europe -where such arrangements have been extensively studied (e.g., Bekkers et al, 2009;Ferro and Sorrentino, 2010;Sanderson et al, 2015;Goldkuhl, 2016). In the USA, these shared infrastructure arrangements are of interest in the public administration literature (e.g., Provan and Kenis, 2008;Provan and Lemaire, 2012;Goldkuhl, 2016;Joha and Janssen, 2011;Williams et al, 2009;Fedorowicz et al, 2007).…”
Section: Public Safety Network Literaturementioning
confidence: 99%
“…Networks of public and private organizations are commonplace in Europe -where such arrangements have been extensively studied (e.g., Bekkers et al, 2009;Ferro and Sorrentino, 2010;Sanderson et al, 2015;Goldkuhl, 2016). In the USA, these shared infrastructure arrangements are of interest in the public administration literature (e.g., Provan and Kenis, 2008;Provan and Lemaire, 2012;Goldkuhl, 2016;Joha and Janssen, 2011;Williams et al, 2009;Fedorowicz et al, 2007).…”
Section: Public Safety Network Literaturementioning
confidence: 99%
“…A number of studies have identified variables that are likely to influence collaborative efforts (see, e.g., Bryson et al, 2006). There have also been multiple studies documenting collaborative efforts in particular cases and types of cases (Artigas et al, 2009;Kellogg, 2009;Williams et al, 2009). Studies addressing public-private nonprofit collaborative partnerships seem to be particularly common (Agranoff, 2006;Agranoff & McGuire, 2003;Berman, 1996;Billett, Ovens, Clemans, & Seddon, 2007;Radin et al, 1996).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Technological efforts refers to the efforts resulting from the degree of technological difficulty and costs of adopting the IOP requirements [6,65,[71][72][73][74]. Organisational efforts are the required efforts to fit the IOP requirements into organisational structures and processes, including efforts related to intraorganisational structures and processes as well as efforts related to the interfacing of organisational structures and processes with those of partnering organisations [cf.…”
Section: Theoretical Frameworkmentioning
confidence: 99%